2004
DOI: 10.1590/s0102-311x2004000700009
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade do Sistema de Informações sobre Nascidos Vivos Hospitalares no Município do Rio de Janeiro, 1999-2001

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 17 publications
0
5
0
8
Order By: Relevance
“…The reliability of SINASC data has been well documented for birth weight and Apgar score in recent studies. 14,20 In fact, 88% agreement was seen between maternity records and SINASC data for birth weight and Apgar score (data not shown). In the year of 2000 in Goiânia, data on birth weight and 5-min Apgar score were missing in the SINASC only in 0.4% and 1.1% of the records, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The reliability of SINASC data has been well documented for birth weight and Apgar score in recent studies. 14,20 In fact, 88% agreement was seen between maternity records and SINASC data for birth weight and Apgar score (data not shown). In the year of 2000 in Goiânia, data on birth weight and 5-min Apgar score were missing in the SINASC only in 0.4% and 1.1% of the records, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…14,20 Thus, SINASC has been linked with the mortality information system (SIM) to assess variables related to neonatal death. 1,15 The cost-effectiveness of preventive programs in developing areas should be maximized, and there should be a continuous search for more accurate variables of neonatal risk.…”
Section: Vigilância De Mortalidade Neonatal a Variável De Efeito Foimentioning
confidence: 99%
“…24 An indirect method to estimate small preterm birth rate was chosen because it is not clear whether SINASC data is valid for the estimation of preterm birth rate. Although a study concluded that there was good agreement on gestational age between SINASC and data from a population-based study, 23 another study found poor agreement between SINASC and cohort data.…”
Section: Brazil Is Divided Intomentioning
confidence: 96%
“…Ausência quase total do registro de peso e altura materna nos prontuários médicos foi encontrada em estudo realizado no município do Rio de Janeiro entre julho de 1999 e fevereiro de 2001, nos estratos 1 (hospitais municipais e federais) e 2 (hospitais privados conveniados com o SUS, militares, estaduais e filantrópicos). 12 Também o número de consultas de pré-natal foi preenchida somente em cerca de metade dos prontuários avaliados no Rio de Janeiro, 12,21 enquanto no SIP-CLAP essa variável teve maior completude (75% no Hospital 1 e 95% no Hospital 2).…”
Section: Discussionunclassified
“…Para que um sistema de informação possa ser utilizado com os objetivos para os quais ele foi desenvolvido é necessário que as informações registradas sejam completas e confiáveis. 11 A completude, medida como proporção da presença de registros em relação ao total de variáveis a ser registrada, e a confiabilidade da informação em relação ao registro das variáveis em prontuários médicos convencionais são metodologias correntemente utilizadas em estudos brasileiros de avaliação da qualidade da informação do SINASC 21,22 e do SIM. 13 Por outro lado, em relação ao SIP-CLAP, não foram localizados estudos similares de avaliação da sua completude e confiabilidade, exceto do banco de dados eletrônico divulgados em manuais do programa.…”
Section: Introductionunclassified